Lignans and other constituents from aerial parts of Haplophyllum Villosum. - Parhoodeh, Parimah; Rahmani, Mawardi; Mohd Hashim, Najihah; Md.Sukari, Mohd. Aspollah; Ee, Gwendoline Cheng Lian (MDPI, 2011)
During our phytochemical investigation of Haplophyllum villosum (Rutaceae), a perennial herb from Iran, a new 4,8-diaryl-3,7-dioxobicyclo-(3,3,0)-octane type lignan, eudesmin A (1), together with four known compounds-eudesmin (2), haplamine (3), umbelliferone (4) and scopoletin (5)-were isolated from aerial parts of the plant. The structures of the compounds were elucidated using NMR spectral analysis (1H-NMR, 13C-NMR, HSQC, COSY and HMBC) as well as UV, IR and MS spectra and comparison with previously reported data.